Biogeochemical properties of seawater measured from the icebreaker Shirase during the 56th Japanese Antarctic Research Expedition in the austral summer, 2014–2015 - TAKAMURA, Tomomi R.; TAKAHASHI, Kunio T.; IIDA, Takahiro; ODATE, Tsuneo (2016)
P(論文) Figure 1,2 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_183_0001_2015.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_183_0002_2015.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_183_0003_2015.doc Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_183_0004_2015.doc departmental bulletin paper